A New Group Acceptance Sampling Plans based on Percentiles for the Weibull Fréchet Model (Statistics, Optimization & Information Computing, 2022)
When the life test is truncated at a pre-determined duration, group acceptance sampling plans for the WeibullFrchet distribution percentiles are introduced in this article. Under a given group size, acceptance limit, and customer risk, the minimum number of groups needed to guarantee the specified life percentile is calculated. The operating characteristic values are discovered, additionally the producer’s risk. To illustrate the process mentioned here, two experimental are given. Also, real data set is used to demonstrate the flexibility of the Weibull Frchet model.